Parental knowledge and care-seeking practices towards pediatric ear infections: a study from Iraq - Aqil Mohammad Daher; Abdulla Alnakshabandi; Khaled Hashim Sultan; Basim A.Al-Abdely; Allya Mohammad Ali (International Journal of Public Health Science (IJPHS), 2022)
An ear infection (EI) is one of the most common pediatric illnesses. This study aimed to assess parental knowledge, care-seeking practices, and factors associated with them. A cross-sectional study involved a sample of parents attending hospitals in three selected cities in Iraq. Data were collected with a questionnaire composed of three parts: i) Sociodemographic characteristics, ii) Questions related to knowledge of symptoms, risk factors, and complications of an EI, and iii) Questions related to care-seeking practices. The mean age of respondents was 34.99 (±9.85) years. Females made up 58.90% of the sample. More than half reported holding tertiary education. Most participants showed satisfactory knowledge of EI symptoms (88.10%) and proper practices of seeking medical attention from a doctor or other medic (95.80%). Respondents with tertiary education had higher odds of having satisfactory knowledge (OR 4.63, 95% CI 1.18-18.19) and proper care-seeking practices (OR 14.96, 95% CI 1.12-28.80) than those with primary education and below. Current smokers had higher odds of having unsatisfactory knowledge (OR 0.12, 95% CI 0.02-0.70) than non-smokers. In conclusion, respondents had sufficient knowledge and care-seeking practices. Educational level was associated with adequate knowledge and care-seeking practices, and former smoking status was associated with unsatisfactory knowledge.